2010
DOI: 10.1038/labinvest.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology by optical methods: spectral cytopathology of the oral mucosa

Abstract: Spectral cytopathology (SCP) is a novel approach for diagnostic differentiation of disease in individual exfoliated cells. SCP is carried out by collecting information on each cell's biochemical composition through an infrared micro-spectral measurement, followed by multivariate data analysis. Deviations from a cell's natural composition produce specific spectral patterns that are exclusive to the cause of the deviation or disease. These unique spectral patterns are reproducible and can be identified and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 21 publications
5
75
1
1
Order By: Relevance
“…Preliminary results on oral SCP from a smaller cohort of patients and volunteers were previously reported [76,75,84]. This study demonstrated small differences in spectral features observed for different anatomical regions of the oral cavity, and a clear differentiation between normal and cancer cells.…”
Section: Scp Results For the Oral Mucosasupporting
confidence: 63%
See 1 more Smart Citation
“…Preliminary results on oral SCP from a smaller cohort of patients and volunteers were previously reported [76,75,84]. This study demonstrated small differences in spectral features observed for different anatomical regions of the oral cavity, and a clear differentiation between normal and cancer cells.…”
Section: Scp Results For the Oral Mucosasupporting
confidence: 63%
“…These developments have led to several studies which detailed application of the methodology to both cervical and oral squamous cells [23,[82][83][84]. Based on the success of these studies, an expanded pre-clinical trial was carried out at the LSpD, the results of which will be presented in this section.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this technology can aid in the accurate diagnosis of cancers that are difficult to distinguish on a morphological basis alone, and whose accurate diagnoses determine therapeutic options. This report follows similar studies from the same laboratory in which equivalent methods for the analysis of exfoliated cells were reported, [29][30][31] using a methodology referred to as spectral cytopathology (SCP). SCP proved to be more sensitive than classical cytopathology in that morphologically normal cells from abnormal (dysplastic) samples exhibited spectral changes that could be associated with a transition from normal to pre-cancerous states.…”
mentioning
confidence: 59%
“…According to their studies, the advantages of SCP are the possibility of monitoring the biochemical arrangement of particular cells, and analyzing the spectral information. This mathematical process provides an impartial, recurrent approach to help cytopathologists and to increase the standard of care for the patient [15].…”
Section: Improvements In Exfoliative Cytologymentioning
confidence: 99%